PERSPEKTIF PENGEMBANGAN MANAJEMEN PEMASARAN SAYURAN DI BALI: KASUS DI DESA PANCASARI KABUPATEN BULELENG - I DEWA GEDE RAKA SARJANA (SOCA: Jurnal Sosial Ekonomi Pertanian, 2007)
ABSTRACT The system approach always looks for integrity among sectors through a whole understanding, therefore, a newer framework known as an approach of the system, is needed. This research is designed to find out variables, that solving the problems by identifying variables that has contextual relationship towards integrated market system, so that the model of the impact can be concluded. The result of study shows eight elements of the system that has been identified, they are: social sector, necessities of program, constraint, enables change, target of program, yardstick, and the activities required, and linked institution. Analysis of sub-element comparison resulting key variable, they are: farmer from business agent element; constructor of the agent, capital guarantee, and government support as the program requirement; risks distribution and inequitable profit as the constraint; guarantee of quality, quantity, cost, and market as the enable change; market share as target of the program; development of incentive system as the necessary activity; and all the linked institutions except the whole sale. From the discussion that is done by the expert, it can be synthesized five criteria of partnership patterns, they are: risk distribution and fair profit, extending job opportunity, increasing of farmer income, make-up of human resources skill and guarantee of quality, quantity, and continuity of production. It is therefore, SUB- KONTRAK was chosen as the priority of alternative partnership pattern that is most appropriate with the formed criteria. Key word: Structure System, Partnership, and Agribisnis Vegetables ABSTRAK Pemikiran sistem selalu mencari keterpaduan antar bagian melalui pemahaman yang utuh, maka diperlukan kerangka pikir baru yang dikenal sebagai pendekatan sistem. Pendekatan ini berupaya untuk menyelesaikan persoalan yang dimulai dari proses identifikasi sejumlah kebutuhan sehingga menghasilkan suatu operasi yang efektif. Hasil kajian terhadap struktur sistem diidentifikasi delapan elemen sistem yaitu : sektor masyarakat, kebutuhan program, kendala, perubahan yang dimungkinkan, tujuan program, tolak ukur, aktifitas yang dibutuhkan dan lembaga terkait. Analisis pembandingan antar sub-elemen diketahui peubah kunci berikut yaitu : petani dari elemen pelaku usaha, pembinaan pelaku, penjaminan modal dan dukungan pemerintah sebagai kebutuhan program, distribusi resiko dan keuntungan yang tidak adil sebagai kendala, jaminan kualitas, kuantitas dan pasar sebagai perubahan, pangsa pasar sebagai tujuan program serta tolak ukurnya adalah meningkatnya kualitas SDM. Dari hasil diskusi para ahli disintese lima kriteria pola kemitraan yaitu : distribusi resiko dan profit yang adil, memperluas kesempatan kerja, peningkatan pendapatan petani, peningkatan keahlian SDM dan jaminan kualitas, kuantitas serta kontinyuitas produksi, sehingga selanjutnya dipilih pola SUB-KONTRAK sebagai prioritas alternatif pola kemitraan yang paling sesuai dengan kriteria yang dibentuk. Kata Kunci: Struktur Sistem, Kemitraan, Agribisnis Sayuran